Prevalence and determinants of smoking among rural young males of Kancheepuram district, Tamil Nadu: a cross sectional study - M., Arunkumar; S., Gopalakrishnan; R., Umadevi (International Journal Of Community Medicine And Public Health, 2019)
Background: Tobacco is the leading global cause of preventable death which kills millions of people and causes huge economic damage every year. Smoking form of tobacco is a major modifiable risk factor for number of chronic non-communicable diseases. In spite of various statutory warnings, smoking still remains a major Public health problem especially in young males. In order to reduce the magnitude and for effective control, the risk factors and distribution should be well known. This study was planned with the objective of assessing the prevalence and determinants of smoking among rural young males of Kancheepuram district, Tamil Nadu, India. Methods: This community based cross sectional study was carried out between March and May 2018 among rural young males aged between 18 to 29 years. Sample size of 431 was calculated by using 4PQ/L2 and the respondents were selected from sampled households using systematic random sampling. Data were collected using a pre-tested, structured questionnaire, which were analyzed using SPSS version 16.0 and presented using descriptive and analytical statistics. Results: Among 422 participants interviewed, the prevalence of smoking was 23%. Factors found to be protective against smoking were employment status and sedentary type of jobs. Factors found to be significantly associated with smoking were individuals with smoking friends and family members, habit of alcoholism, employment and low education status. Conclusions: Since smoking is a preventable cause of morbidity and mortality, efforts should be made to control its use by intensive health education, implementing counsellingfacilities and rigorous enforcement of anti-tobacco legislation.